Expression and immunogenicity determination of recombinant clone of pasteurella multocida serotype B against haemorrhagic septicaemia: towards a vaccine development - Abdullah, M.A.; Hussaini, J.; Ismail, S. (Medwell Online, 2012)
Clone ABA392 is virulent to mice and is capable of producing HS like symptoms. Balb/C mice were injected with various forms of vaccine (live and killed) and vaccination schedules in order to determine the immunogenicity of the clone. The immunized animals were challenged with lethal dose of Pasteurella multocida serotype B and at the same time a Passive Mice Protection Test (PMPT) was also carried out. Protection of 66 and 83% was achieved in mice vaccinated with live and killed forms, respectively. In PMPT, 66% of mice passively immunized with immune sera were protected. By performing ELISA test, it was found that the triple dose vaccination elicited high antibody production in the vaccinated animals. There was significant increase (p<0.05) antibody production in triple dose vaccination compared to double dose vaccination. The clone ABA392 was sub-cloned into an expression system. The sub-clone (CSI57J) was expressed and with the help of immuno-detection method (chromogenic method) specific to His-tagged expressed protein, the expression was confirmed. The expressed protein was extracted, purified and quantified and subsequently subjected to SDS-PAGE for size detection. The protein size was found to be about 26 kDa. Mice were immunized with the expressed protein and the effect of direct and passive immunization was determined. In direct immunization, 90% of mice were protected from lethal dose of P. multocida serotype B and on the other hand, 83% protection was observed in passively vaccinated mice. This study shows that the expressed sub-clone CSI57J has the potential to be a good candidate for a new recombinant vaccine against HS.